Effectiveness of English E-Learning Classes: University Students’ Perspectives - Malkawi, Nibal A. M.; Rababah, Luqman Mahmoud; Erkir, Sarp; Bani-Khair, Baker; Al-Hawamdeh, Basma Mohammad; Al-Omari, Sana Kamel; Rababah, Mahmoud Ali (Journal of language teaching and research, 2024)
Owing to technological growth, new educational models have emerged that depend on technical advancements to accomplish learning goals. One of the applications that stand out is e-learning, which has altered both the roles and duties of instructors and students, as well as the way traditional education is conducted in academic institutions. This study investigates how Jordanian university students view the value of the online courses they take. A questionnaire with ratings for the quality of e-learning and students’ satisfaction was used to collect the data. The study’s sample consisted of 566 university students from Al-Balqa Applied University, Jordan. The findings indicated that the e-learning courses' overall content quality was average. The quality of the form of the e-learning lessons was high, and the students' degree of satisfaction with the quality of the e-learning courses was moderate. The study found that the most effective way to facilitate learning is to present courses in a clear hierarchy or framework.